Propuesta didáctica para la enseñanza de inecuaciones cuadráticas en el marco funcional - Huamán Tafur, Aarón Juan (2025)
Several studies report that students have difficulties when approaching algebraic tasks with strictly algebraic procedures based on the axioms of real numbers. In particular, solving quadratic inequalities with one unknown is usually approached using a sign algorithm, which does not help understand the subject matter. This paper explores the effect that the use of GeoGebra may have as a teaching alternative to overcome the limitations of traditional teaching of quadratic inequalities. This is done by studying linear and quadratic functions, the articulation of representations in graphical and algebraic registers, as well as the shift from algebraic to functional frameworks. The comparison between theoretical planning, practical development in the classroom, and final reflection reveals that the teaching sequence designed facilitated the understanding of the method for determining the solution set of quadratic inequalities.